Macroinvertebrados aquáticos como indicadores de qualidade de água em viveiros de psiculturas em Santarém-PA - DUARTE, Fabricia Braga (Universidade Federal do Oeste do Pará, 2021)
In general, measurements of physico-chemical variables are used to determine the quality of water in fish farming. However, these are punctual, with more representative effects when associated with biological indicators. Water quality variables can reflect on growth, reproduction, health, survival and quality of fish, compromising the success of aquaculture systems, hence the importance of evaluating and monitoring breeding systems. The objective of this study was to determine the efficiency of aquatic macroinvertebrate fauna to be used in the biomonitoring of water quality in fish farms in the municipality of Santarém - PA, in addition to testing the application of the Family Biotic Index (IBF) of the water in these nurseries. Samplings of the macroinvertebrates were carried out in 17 nurseries of three fish farms that work in Santarém - PA, during the months of November to December 2017. A total of 1,016 larvae of aquatic macroinvertebrates were collected, distributed in 15 genera, 10 families and six orders. The Diptera order was the most representative with 821 specimens. Of the variables analyzed, temperature, dissolved oxygen in water, potassium K and clay were significantly related to insect abundance. It was verified, also by half of the multiple linear regression, that there is no trend of the metric wealth of aquatic insects is related to any of the environmental variables sampled.